Partisipasi Masyarakat Dalam Perencanaan Pembangunan Di Kampung Trikora Distrik Benawa Kabupaten Yalimo. - Oben Wisabla; James Modouw; Lazarus Ramandei (Fakultas Teknik Universitas Cenderawasih, 2024)
This research is entitled Community Participation in Development Planning in Trikora Village, Benawa District, Yalimo Regency. Community participation in Trikora Village, Benawa District, Regency is still very lacking. Because if you look at the level of participation such as thoughts, skills, goods and money, it is still very lacking, but participation in terms of community energy is very enthusiastic. Apart from that, the main factors that influence the level of community participation are age level, length of stay, intensity of interaction and type of leadership.The results of this research are that there are five levels of community participation in village development, namely thought, energy, expertise, goods and money. The participation that can be carried out by the community is participation in terms of thinking, because in other matters the people of Trikora village are still very limited in their abilities. There are two factors that influence the level of community participation in development in Trikora Village, namely internal and external which are described by age level, length of stay, intensity of interaction, and type of leadership. The age level of the community in Trikora village greatly influences the low level of participation, the length of stay is also very influential because it is directly related to the community's emotional ties to where they live. The intensity of interaction also influences low participation in Trikora village and the level of autocratic leadership makes people reluctant to participate in developing Trikora village.